Endoscopic Resections in Inflammatory Bowel Disease: A Multicentre European Outcomes Study. (17th April 2019) - Alkandari, A; Thayalasekaran, S; Bhandari, M; Przybysz, A; Bugajski, M; Bassett, P; Kandiah, K; Subramaniam, S; Galtieri, P; Maselli, R; Spychalski, M; Hayee, B; et al.
Abstract: Background and Aims: Inflammatory bowel disease is associated with an increased risk of colorectal cancer, with estimates ranging 2–18%, depending on the duration of colitis. The management of neoplasia in colitis remains controversial. Current guidelines recommend endoscopic resection if the lesion is clearly visible with distinct margins. Colectomy is recommended if complete endoscopic resection is not guaranteed. We aimed to assess the outcomes of all neoplastic endoscopic resections in inflammatory bowel disease. Methods: This was a multicentre retrospective cohort study of 119 lesions of visible dysplasia in 93 patients, resected endoscopically in inflammatory bowel disease. Results: A total of 6/65 [9.2%] lesions <20 mm in size were treated by ESD [endoscopic submucosal dissection] compared with 59/65 [90.8%] lesions <20 mm treated by EMR [endoscopic mucosal resection]; 16/51 [31.4%] lesions >20 mm in size were treated by EMR vs 35/51 [68.6%] by ESD. Almost all patients [97%] without fibrosis were treated by EMR, and patients with fibrosis were treated by ESD [87%], p < 0.001. In all, 49/78 [63%] lesions treated by EMR were resected en-bloc and 27/41 [65.9%] of the ESD/KAR [knife-assisted resection] cases were resected en-bloc, compared with 15/41 [36.6%] resected piecemeal. Seven recurrences occurred in the cohort. Seven complications occurred in the cohort; six were managed endoscopically and one patient with a delayed perforation underwent surgery. Conclusions: Larger lesions with fibrosis are best treated by ESD, whereas smaller lesions without fibrosis are best managed by EMR. Both EMR and ESD are feasible in the management of endoscopic resections in colitis.